THE HEROINE’S JOURNEY OF NORA SEED IN MATT HAIG’S THE MIDNIGHT LIBRARY - Andayani, Ambar; Nero Surya Wijayanto, Maulana (La Ogi : English Language Journal, 2026)
This study analyzes the heroine’s journey of the female main character in Matt Haig’s The Midnight Library. The purpose of this research is to examine the emotional, and character development of the female main character as she navigates her inner struggles and life choices. The study applies Maureen Murdock’s theory of The Heroine’s Journey to understand how the protagonist experiences separation from her feminine identity, confronts internal conflict, and ultimately achieves healing and self-acceptance. This research focuses on key aspects of the heroine’s journey, including regret, emotional pain, and the process of reconciliation with the self. this study explores the feminism values reflected in the female main character’s journey, such as independence, emotional resilience, self-acceptance, and the balance between feminine and masculine traits. These values highlight how the novel presents female empowerment not through physical strength or external success, but through inner awareness and emotional growth. The method used in this research is qualitative, with the novel serving as the primary data source. Data are analyzed through close reading and interpretation based on Murdock’s theoretical framework. The findings show that the main character’s journey follows the stages of the heroine’s cycle, beginning with separation, continuing through trials, despair, concluding with integration, and self-understanding. The study concludes that The Midnight Library presents a modern representation of female heroism that emphasizes personal healing, self-discovery, and the importance of choosing life. Through this journey, the novel encourages readers to reflect on identity, regret, and the possibility of growth through acceptance.